Análise da segregação axial e radial em um leito de jorro cônico - Morais, Jéssika Nayara Santos (2020)
The particle cyclic and orderly movement inside a spouted bed has as main advantages of this technique, thus enabling an effective particle-particle and fluid-particle contact, which results in high transfer rates of heat, mass and movement. Due to their intrinsic characteristics, spouted beds have been widely used in industrial processes, however, there are some disadvantages operation inherent, the most complex of which are related to the segregation phenomenon, which occurs due to the multicomponent mixtures use in production lines, causing a non-uniform product formation, which compromises the equipment performance. In this way, a better understanding of the segregation phenomenon inside a spouted bed, is of fundamental importance for its design, operation and optimization. In the present work, a non-intrusive methodology using a solidification-slicing approach was used for the investigation of radial and axial segregation behavior in a spouted bed. The effects of diameter, density, and shape of the particles, as well as the initial particle loading, and the inlet air velocity, on segregation were qualitatively and quantitatively assessed. Regarding the results, binary mixtures with aspect, diameter and density ratios, equals a 2.0, 2.0, and 1.9, respectively, show a random mixture condition. Binary mixtures with diameter ratio of 4.5 and density ratio of 5.8, show radial and axial segregation. As regards to radial segregation, the higher or denser particles, tended to form a central core at the spout region, and the smaller or lighter particles, flowed to the annular region near the spouted bed wall. The particle dynamics seemed not to be significantly affected by changing the particle initial loadings in systems with aspect ratio of 2.0 and density ratio of 5.8, however, affected systems with diameter ratio of 4.5. As expected, the increase in diameter and density ratios caused an increase in radial and axial segregation. The segregation phenomenon for binary mixtures with high density ratio, were shown to be dependent of the initial particle loading configuration, but independent of the superficial gas velocity.